Physiological responses in supramaximal high-intensity intermittent training in young competitive cyclists - Nicolò, A.; Bazzucchi, I.; Lenti, M.; Haxhi, J.; Scotto di Palumbo, A.; Conti, A.; Sacchetti, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
High intensity intermittent training (HIT) is recognized to be the preferential type of exercise to elicit further adaptations in already highly-trained endurance athletes (Laursen and Jenkins, 2002). However, the acute physiological responses of HIT protocols remain to be fully explored. We investigated two types of supramaximal HIT protocols used by some cycling coaches to notably stress both the aerobic and anaerobic metabolism. Methods: Thirteen competitive cyclists (19 ± 2 yr, VO2max of 63.1 ± 4.2 ml/kg/min) performed a maximal incremental test and two randomized HIT protocols to exhaustion during the competitive season. HIT protocols differed in work and rest duration (40 s:20 s and 30 s:30 s) but had the same work (135% of peak power output) and rest (0 W) intensity. Gas exchange and ventilatory parameters, heart rate (HR), blood lactate [La-] and surface electromyographycal (sEMG) parameters (root mean square and muscle fibre conduction velocity) from the vastus lateralis (VL) muscle were collected. Results: Time to exhaustion was 10 ± 3 min and 38 ± 13 min, and average VO2 was 89 ± 4% and 75 ± 4% of VO2max for 40 s:20 s and 30 s:30 s, respectively. Maximum values of VO2 and ventilation (Ve) for 40 s:20 s were significantly higher (p < 0.01) than those of the other two trials. Peak [La-] value was significantly higher (p < 0.01) for 40 s:20 s than for 30 s:30 s (13 ± 1.5, 10 ± 2.9) while mean values of [La-] for 30 s:30 s were at or above the 8 mmol/l value for about 20 min. The kinetics of Ve as a function of time was incremental while that of VO2 was quite stable throughout the test, except for a slight but significant (p < 0.05) decrease in the last part of the trial. The HR kinetics showed a cardiac drift. All the kinetics described were similar between the two HIT tests. The EMG analysis indicated a substantial neuromuscular involvement of the VL but did not detect significant changes in the sEMG parameters kinetics during the two trials. Discussion: In the two HIT tests, the metabolic and ventilatory parameters seemed to better explain athlete exhaustion than the neuromuscular ones. The aerobic and anaerobic metabolism appeared highly stimulated, although in different ways, due to the different mean total exercise duration. The 40-s:20-s test enabled physiological parameters to reach maximum values, while the 30-s:30-s one stimulated the lactate tolerance, allowing to maintain quite high [La-] levels for a long period of time. Moreover, both the HIT tests provide an important tool to reach high levels of Ve. These results can help coaches and exercise scientists choose and prescribe supramaximal HIT protocols